Quality Control of Lead-Acid Battery according to Its Condition Test for UPS Supplier and Manufacturers. (25th September 2014) - Hsiao, Tsung-Chih; Chen, Tzer-Long; Liu, Chia-Hui; Lee, Chih-Ming; Yu, Hsin-Chun; Chen, Tzer-Shyong
Abstract : The risk of insufficient petroleum resources has forced human beings to emphasize the acquisition and storage of energy. To avoid such situation, this study tends to explore the effective management of lead-acid batteries for effective utilization conforming to the industrial requirements.